Effect of Gypsum in Reducing Boron Hazard of Saline Waters and Soils - Gupta, I C; Chandra, Harish (Annals of Arid Zone, 2016)
Use of gypsum has been found to reduce boron hazard of saline waters and a saline sodic soil. One percent dose of gypsum for waters and eighty percent dose of gypsum requirement for a saline-sadic soil were found adequate to reduce toxic concentration of boron to non-toxic levels.